1968
DOI: 10.1099/00221287-54-3-417
|View full text |Cite
|
Sign up to set email alerts
|

Elimination by Ethidium Bromide of Antibiotic Resistance in Enterobacteria and Staphylococci

Abstract: SUMMARYEthidium bromide, a trypanocidal drug affecting nucleic acid synthesis, was found to be a powerful agent in eliminating some antibiotic resistance in bacteria. In staphylococci, penicillinase production was eliminated in mercury-resistant organisms, but not in mercury-sensitive ones. Among enterobacteria, two resistance factors showing the same resistance pattern were differently eliminated, and correlation between elimination and transfer of resistance factors was not always observed. F'-lac+ factor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(92 citation statements)
references
References 13 publications
2
90
0
Order By: Relevance
“…Pla,smid curing Treatment of cultures with ethidium bromide (Bouanchaud, Scavizzi & Chabbert, 1969), acridine orange (Watanabe & Fukasawa, 1961) or SDS/high temperature (Hill & Carlisle, 1981) were the methods used to obtain plasmid curing.…”
Section: Plasmid Dna Isolationmentioning
confidence: 99%
“…Pla,smid curing Treatment of cultures with ethidium bromide (Bouanchaud, Scavizzi & Chabbert, 1969), acridine orange (Watanabe & Fukasawa, 1961) or SDS/high temperature (Hill & Carlisle, 1981) were the methods used to obtain plasmid curing.…”
Section: Plasmid Dna Isolationmentioning
confidence: 99%
“…However, the heterogeneity of the molecules and the variable number of single-strand breaks suggested that the isolated mDNA was the degradative product of a larger, possibly circular species . Finally, bacterial episomes, which are eliminated by EtBr (Bouanchaud, Scavizzi, and Chabbert, 1969), are probably coded by closed circular DNA . Thus, available data are consistent with the proposition that the synthesis of closed circular DNA is more sensitive to EtBr than the synthesis of linear DNA .…”
Section: Resultsmentioning
confidence: 99%
“…Growth of plasmid-containing strains of Staphylococcus aureus in the presence of ethidium bromide results in loss of the plasmid (Bouanchaud, Scavizzi & Chabbert, 1968). The experiment on stability was repeated in the presence of 9 x I O -~ M-ethidium bromide.…”
Section: Resultsmentioning
confidence: 99%